Indian politics - Sáez, Lawrence (Henry Stewart Talks, 2011)
India's constitution, National government structure, The legislative branch, Federal structure, State government structure, India's political structure, India as a democracy, Indira Gandhi's role in Indian politics, Decline and revival of Congress dominance, Caste in India's politics, Emergence of caste-based parties, Emergence of a Hindu nationalist party, India's economic liberalisation and globalisation, India's demographic challenges